Analyzing Harmonic Reduction in Grid-Connected PV Systems through LCL Filtering Techniques (ELEKTRIKA- Journal of Electrical Engineering, 2025)
As the integration of photovoltaic (PV) systems into power grids increases, effectively managing harmonic distortion becomes essential for ensuring power quality and system reliability. This study examines the performance of L and LCL filters in reducing harmonic distortion in a grid-connected PV system, focusing on their impact under different loading conditions. A comprehensive simulation was conducted using a 3 MW PV system connected to a 400 V, 50 Hz grid. The analysis involved three scenarios which are case A: an L filter with a linear load, case B: an L filter with a non-linear load and case C: an LCL filter with a non-linear load. The study found that non-linear loads significantly elevated harmonic distortion levels, with the THDI increasing from 7.56% (linear load) to 14.58% (non-linear load). However, the application of the LCL filter effectively reduced harmonic distortion, bringing THDI down to 7.02%. These findings highlight that while linear loads produce lower harmonic distortion, the LCL filter is more effective in maintaining power quality in systems subjected to non-linear loads.
Keywords: harmonics; LCL filter; grid-connected PV system; power quality